دور المصرف الصناعي في التنمية الصناعية في سورية - بوحسون ياسر; درويش خير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث وبالتحليل الاقتصادي – القياسي واقع القطاع الصناعي في سورية بالوقت نفسه واقع المصرف الصناعي ودوره في تنمية القطاع الصناعي. من خلال هذه الدراسة توقفنا على أهم المعوقات التي أسهمت بعرقلة تطور القطاع الصناعي, وانعكست سلباً على كفاءته وأدائه الاقتصادي, ومن جهة أخرى قمنا بدراسة الأسباب الرئيسة التي أدت إلى ضعف أداء المصرف الصناعي وقصور دوره في تنمية القطاع الصناعي في سورية. لنتوصل بنتيجة البحث إلى عدد من الحلول والمقترحات التي يمكن أن تسهم بزيادة فعالية وكفاءة وأداء المصرف الصناعي ليلعب دوراً أكثر فعالية في تنمية القطاع الصناعي, باعتباره من أهم القطاعات الاقتصادية المحركة لباقي القطاعات ولعملية التنمية الاقتصادية والاجتماعية. This paper analyzes the status of industrial sector in Syria, and role of the Industrial Bank in developing the industrial sector. It focuses on the most serious obstacles that contribute to hindering the growth of the industrial sector and negatively its economical performance and efficiency. Moreover, the paper tries to explain the main reasons that lead to weakening the developing role of the Industrial Bank. The paper concludes with some suggestions that may help in increasing the effectiveness and efficiency of he Industrial Bank to take its real role in developing the industrial sector. The sector is very important because of its high contribution to the GDP.